Role of additive manufacturing applications towards environmental sustainability - Javaid, Mohd; Haleem, Abid; Singh, Ravi Pratap; Suman, Rajiv; Rab, Shanay (Advanced industrial and engineering polymer research, 2021)
Additive manufacturing (AM) produces a complex shaped product from its data, layer by layer, with high precision and much less material wastage. As compared to the conventional manufacturing process, there are many positive environmental advantages of additive manufacturing technologies. Most importantly, there is less waste of raw material and the use of new and smart materials. It appears to concentrate on the output of a component on lesser material waste, energy usage, and machine emissions. There is a need to study the environmental sustainability of additive manufacturing technologies and their applications. As more businesses aim to strengthen their eco-footprint, sustainability in AM is gaining momentum. Visionary leaders of the industry are continually challenging their employees to find new ways to reduce waste, improving their workforce's manufacturing environment, and find innovative ways to use new materials to become more sustainable. The growth in value-added components, goods, and services has resulted from these initiatives. This paper discusses the significant benefit of additive manufacturing to create a sustainable production system. Finally, the paper identifies twelve major applications of AM for sustainability. Although additive manufacturing and technological dominance are being established with crucial industries, their sustainability advantages are visible in the current manufacturing scenario. The main goal is to identify the environmental benefits of additive manufacturing technologies over conventional manufacturing. Industries can now decide on suitable technologies to meet environmental goals.